Leukocyte function in vitro after adding vitamins A, E, and Beta-Carotene - S.D. Eicher; J.L. Morrill; Frank Blecha (Kansas Agricultural Experiment Station Research Reports, 1992)
Blood neutrophils and pulmonary alveolar macrophages isolated from calves at 3 and 6 wk of age were cultured in medium without added vitamins or supplemented with vitamin A, vitamin E, vitamin A and vitamin E, or ßcarotene and vitamin E. Macrophage bactericidal activity improved with A-E supplementation compared to ß-carotene-E supplementation at wk 3. Neutrophil bactericidal activity decreased with all vitamin E treatments at wk 3 and with vitamins E and A-E at wk 6. Neutrophil phagocytosis improved at wk 3 with A, E, and A-E supplementations. The chemotactic index improved at wk 3 with ß-carotene- E compared to vitamin E alone and at wk 6 with vitamin E compared to vitamin A and control treatments. The retinol content of neutrophils at wk 3 was variable, but by wk 6, cells supplemented with A, E, or A-E had higher retinol concentrations than control cells. Neutrophil a-tocopherol concentrations at 3 wk increased over controls with vitamin E or ßcarotene- E supplementation, but at wk 6, vitamin E-supplemented cells were different only from vitamin A-supplemented cells. These data suggest that there are optimum plasma concentrations of vitamins A and E for leukocyte functions.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Retinol; α-Carotene; Neutrophils; Macrophages; Calves